The Correlation Between Perceived Pesantren Values And Self-Efficacy Towards Student Learning Motivation - Nor Hasan; Mohammad Muchlis Solichin; Wahab Sahirul Alim; Reza Mubarak; Mohammad Hasan (PT. Anagata Sembagi Education, 2025)
This study aims at examining the correlation between values and the students' self-efficacy towards the student learning motivation in the pesantren. This is qualitative research that is performed using statistical analysis. The population was composed of 227 students from the Pondok Pesantren Sumber Mas Ganding in Sumenep and a sample of 145 students was taken from the total. To analyze the data, multiple linear regressions performed by classic regression assumption and hypothesis evaluations comprising Concurrent and Partial Tests were used. After testing, a coefficient of determination (R2) was formed to determine the suitability of the regression model. The results showed that all Sig. were greater than α = 0.05. Therefore, the pesantren values and the students' learning efficacy were shown to have significant effects on learning motivation. Also, an increase in pesantren scores and the learning efficacy by one unit each enhanced the motivation by 0.482 and 0.481 respectively.